Spatial Variability of Heavy Metals in Soils and Sediments of “La Zacatecana” Lagoon, Mexico - Sergio A. Covarrubias; Juan Armando Flores de la Torre; María Maldonado Vega; Francisco Javier Avelar González; Juan José Peña Cabriales (Applied and Environmental Soil Science)
Anthropogenic activities have greatly increased heavy metal pollution worldwide. Due to inadequate waste management, mining is one of the chief causes. One particularly affected area in Mexico is the “La Zacatecana” Lagoon, in the municipality of Guadalupe, Zacatecas. From colonial times until the mid-nineteenth century, about 20 million tons of mine tailings were deposited at this site. Here, we catalogue the heavy metal content and their distribution in soils and sediments of La Zacatecana. The mobility of lead in soils was also assayed by sequential extraction. Concentrations of the different metals analysed were as follows: Pb > Cr > As > Ni > Hg > Cd. Site VIII accumulated the highest amount of Pb (3070 mg·kg−1) sevenfold more than the limit established by the Mexican standards for agricultural soils (i.e., 400 mg·kg−1). On the other hand, the contents of Cd, Cr, and Ni were within the levels accepted by the above normativity, set at 37, 280, and 1600 mg·kg−1, respectively. Concentrations of Hg and Pb were highest in the north-northwest zone of the lagoon and decreased towards the southeast. Except for Site VIII where 30% of the Pb was in an interchangeable form or bound to carbonates, most Pb in La Zacatecana soils was present in an unavailable form, associated with Fe-Mn oxides.